Simulasi Kolam Retensi Untuk Mengatasi Banjir Genangan Di Kota Bangkinang Bagian Barat - Bangun Aldilla Rachman; Mudjiatko Mudjiatko; Trimaijon Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Most of the surface run off water in rainy season in Bangkinang flow to Petai I river, and this condition makes the Petai I river unable to deliver it anymore to Kampar river, it will flood some region in Bangkinang. A concept has been developed according to this condition it devides the raining region into two parts for the Jendral Ahmad Yani street, the east region to Petai I river and the west to Polsek Bangkinang channel. Soil permeability is determined to get a rate of infiltration in the retention pond. Soil samples were taken in the location of research using hand auger and then taken to the laboratory for testing permeability values with permeameter. From the test results obtained by the value of the infiltration is 7.44 x10-7 cm/sec. The retention pond is simulated to reduce debit of surface run off, and at the end it will reduce planned channel dimension, also the lands for drainage channel can be reduced. Retention pond are planned about six retention ponds then simulated by reducing the surface run off water approximately20%, but the retention pond size needed is too big ie between 28,7-5000 hectare, that’s why the retention pond size must be suited with the size of the land. After the making of this retention pond, the debit surface run off so small, and it makes the channel dimension stable. So the making of retention pond in west Bangkinang cant be made as alternetive to reduce the surface run off water. Key words :channel dimension, retention pond, surface run off.